All about love : new visions - Hooks, Bell, 1952-2021 (New York : William Morrow, 2018)
A New York Times bestseller and enduring classic, All About Love is the acclaimed first volume in feminist icon bell hooks' "Love Song to the Nation" trilogy. All About Love reveals what causes a polarized society, and how to heal the divisions that cause suffering. Here is the truth about love, and inspiration to help us instill caring, compassion, and strength in our homes, schools, and workplaces. “The word ‘love’ is most often defined as a noun, yet we would all love better if we used it as a verb,” writes bell hooks as she comes out fighting and on fire in All About Love. Here, at her most provocative and intensely personal, renowned scholar, cultural critic and feminist bell hooks offers a proactive new ethic for a society bereft with lovelessness--not the lack of romance, but the lack of care, compassion, and unity. People are divided, she declares, by society’s failure to provide a model for learning to love. As bell hooks uses her incisive mind to explore the question “What is love?” her answers strike at both the mind and heart. Razing the cultural paradigm that the ideal love is infused with sex and desire, she provides a new path to love that is sacred, redemptive, and healing for individuals and for a nation. The Utne Reader declared bell hooks one of the “100 Visionaries Who Can Change Your Life.” All About Love is a powerful, timely affirmation of just how profoundly her revelations can change hearts and minds for the better.
Keywords: Liefde